La organización barrial en los procesos de gestión de la Ciudadela Amazonas 1, parroquia Puerto Bolívar, 2022 - Pérez Suarez, Deyna Lisseth; Jiménez Herrera, Kevin Alexander (Machala: Universidad Técnica de Machala, 2023)
The research explores the types and levels of organization in neighborhoods and management processes. Therefore, the general objective is to determine the impact of neighborhood organization on the management processes in the Amazonas 1 town of the Puerto Bolívar port city, considering that individuals as social beings seek to bring about change in their environment. The specific objectives are focused on identifying the socio-organizational characteristics of the current neighborhood committee, determining the level of residents' participation in the neighborhood management process, and establishing the consequences of the lack of neighborhood organization. On the other hand, it is important to mention that the sociological basis for this research is structural-functionalism. This perspective views the study's problem as an organizational structure, one that is hierarchically arranged and interconnected. With this in mind, every organization serves a specific function and arises in response to a particular need. In the case at hand, it is the neighborhood's management processes that play a vital role in achieving objectives aimed at resolving the issues faced by its citizens. Concerning the epistemological approach of the study, it aligns with the empirical-inductive framework. The research follows a positivist perspective, where knowledge is derived from empirical evidence and experience. This study adopts a basic research approach and utilizes a mixed methodology, combining data collection through surveys and structured interviews with town residents, along with a review of scientific articles in the literature. The research results indicate that the main factor contributing to the inadequate organization is the presence of disagreements and limited communication among the committee citizens. Consequently, this leads to a lack of motivation among residents to participate in the management processes. Therefore, it was identified that insufficient communication is a fundamental factor behind the issue of poor neighborhood organization. In line with this, a proposal has been formulated under the title Project for Leadership and Citizen Participation Training to Strengthen the Organizational Structure of Amazonas 1 town. This project takes on the responsibility of presenting an alternative for implementing strategies that pave the way for suitable conditions in the short, medium, and long term to enhance community organization. Its sociological underpinning draws from Niklas Luhmann's theory of systems, emphasizing that communication generates and sustains society as a systematic social operation. The main objective is to strengthen community organization and leadership through educational workshops, aiming to improve social cohesion and the leadership capacity of the town's leaders. Additionally, it aspires to promote organization through the learning of parliamentary procedures, existing mechanisms of the Council for Citizen Participation and Social Control, the importance of developing skills in neighborhood management, conflict resolution, instruments to enhance leadership skills, and the significance of planning, among others. This will be achieved through cooperation with the Autonomous Decentralized Government of Machala, specifically with the Department of Citizen Participation, to ensure successful work with the residents of the neighborhood.
La investigación explora los tipos y niveles de organización en los barrios y los procesos de gestión, por ello tiene como objetivo general: determinar la incidencia de la organización barrial en los procesos de gestión de la ciudadela Amazonas 1 de la parroquia Puerto Bolívar, teniendo en consideración que el individuo como ser social, busca generar cambio en su entorno, los objetivos específicos se encaminan en identificar qué características socio organizativas tiene la actual directiva, determinar el nivel de participación de los habitantes en el proceso de gestión barrial, establecer las consecuencias de la escaza organización barrial. Por otra parte, se debe mencionar que el fundamento sociológico es el estructural funcional, que busca entender el problema de estudio como una estructura organizacional y que se encuentran estructuradas jerárquicamente e interrelacionadas, dicho eso, toda organización tiene una función que cumplir y que se presenta en torno a una necesidad, siendo estos los procesos de gestión de la organización barrial los que determinen la consecución de objetivos que puedan resolver el problema que atañen a los individuos que la componen. En cuanto al enfoque epistemológico del estudio compete al empírico – inductivo, ya que la investigación es de carácter positivista, es decir, que el conocimiento procede de la experiencia, con un tipo de investigación básica y una metodología cuantitativa, puesto que se recopilará información a través de encuestas y entrevistas dirigidas a los habitantes de la ciudadela, así mismo la revisión bibliográfica de artículos científicos. Los resultados de la investigación determinan que la causa principal para que no se dé una correcta organización, es que existen desacuerdos, escasa comunicación entre la directiva, dando como desenlace que los moradores se desmotiven en participar en los procesos de gestión. Por ello se identificó a la poca comunicación como una pieza fundamental en la causa de la escasa organización barrial. En esa línea se elaboró una propuesta con el nombre de Proyecto de capacitación en liderazgo y participación ciudadana para el fortalecimiento organizacional de la ciudadela Amazonas1, que tiene la responsabilidad de promover una alternativa para la implementación de estrategias que den paso a condiciones apropiadas a corto, mediano y largo plazo, para fortalecer la organización comunitaria, por lo tanto su fundamentación sociológica es la teoría de sistemas de Niklas Luhmann, ya que, menciona que la comunicación produce y reproduce a la sociedad, constituyendo una operación sistemática de carácter social, por ello su objetivo principal es fortalecer la organización y el liderazgo comunitario a través de talleres educativas para mejorar la cohesión social y la capacidad de gestión de los dirigentes de la ciudadela, también se aspira fomentar la organización mediante el aprendizaje de: procedimientos parlamentarios, mecanismos existentes del Consejo de Participación Ciudadana y Control Social, importancia de desarrollar habilidades en la gestión barrial, resolución de conflictos, instrumentos para potenciar las habilidades de liderazgo, importancia de la planificación, entre otros. Esto se realizará con la cooperación del Gobierno Autónomo Descentralizado de Machala, específicamente con el departamento de Participación Ciudadana, para lograr un acertado trabajo con los moradores del barrio.
Keywords: ORGANIZACION BARRIAL; PROCESOS DE GESTION; CIUDADELA AMAZONAS 1; LIDERAZGO COMUNITARIO